Time at Home during the COVID-19 Pandemic: Findings from Focus Groups with Hispanic Parents - Amber J. Hammons; Ryan Robart; Guadalupe Gonzalez (MDPI AG, 2022)
The COVID-19 pandemic upended family life, forcing many families to reorganize their daily routines. Hispanic families have been especially affected by the pandemic, experiencing cumulative stressors and increased risks of contracting the virus, hospitalization, and morbidity. To date, there is limited research examining home life within Hispanic families during the pandemic. Given the extended amount of time for which families have been isolated at home together, identifying factors that may enhance or detract from well-being within the home is important in advancing efforts to support at-risk families. In this qualitative study, 29 Hispanic parents (primarily mothers) living in California participated in one of eight focus groups conducted in Spanish. Parents described activities and behaviors during the first year of the COVID-19 pandemic. The following six themes were identified using reflexive thematic analysis: (1) parents focused on family time; (2) children adapted to the changes of the pandemic; (3) parents and children engaged in physical activity; (4) children mainly entertained themselves with screens; (5) COVID-19 media coverage was accessible in the home; and (6) parents worried about the virus, and its effects on the future. While findings include anxiety around the virus and its attendant effects, family strengths were also present throughout the discussions. Public policy should consider ways to leverage family strengths to preserve family relationships and routines during future public health crises.